Tissue engineering in reconstructive urology—The current status and critical insights to set future directions-critical review - Ławkowska, Karolina; Rosenbaum, Clemens; Petrasz, Piotr; Kluth, Luis; Koper, Krzysztof; Drewa, Tomasz; Pokrywczynska, Marta; Adamowicz, Jan; , the Trauma and Reconstructive Urology Working Party of the European Association of Urology Young Academic Urologists (Frontiers in Bioengineering and Biotechnology, 2023)
Advanced techniques of reconstructive urology are gradually reaching limits in terms of their ability to restore urinary tract function and patients’ quality of life. A tissue engineering-based approach to urinary tract reconstruction, utilizing cells and biomaterials, offers an opportunity to overcome current limitations. Although tissue engineering studies have been heralding the imminent introduction of this method into clinics since over a decade, tissue engineering is marginally applied. In this review, we are discussing the role of tissue engineering in reconstructive urology and trying to answer the question - why such a promising technology didn’t prove its clinical usability so far.